2017
DOI: 10.1038/nature22372
|View full text |Cite
|
Sign up to set email alerts
|

uORF-mediated translation allows engineered plant disease resistance without fitness costs

Abstract: Controlling plant disease has been a struggle for mankind since the advent of agriculture. Studies of plant immune mechanisms have led to strategies of engineering resistant crops through ectopic transcription of plants’ own defence genes, such as the master immune regulatory gene NPR11. However, enhanced resistance obtained through such strategies is often associated with significant penalties to fitness2, making the resulting products undesirable for agricultural applications. To remedy this problem, we soug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
201
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 285 publications
(202 citation statements)
references
References 33 publications
1
201
0
Order By: Relevance
“…Several studies have illustrated the power of altering mRNA translation via uORFs to improve agriculture (13). For example, engineering rice that specifically induces defense proteins when a uORF is repressed by pathogen attack enables immediate plant resistance without compromising plant growth in the absence of pathogens (2). The identification of translated ORFs provides new possibilities to fine-tune the synthesis of proteins involved in diverse physiological pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have illustrated the power of altering mRNA translation via uORFs to improve agriculture (13). For example, engineering rice that specifically induces defense proteins when a uORF is repressed by pathogen attack enables immediate plant resistance without compromising plant growth in the absence of pathogens (2). The identification of translated ORFs provides new possibilities to fine-tune the synthesis of proteins involved in diverse physiological pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent report showed green tissue‐specific expression of master controller AtNPR1 gene in rice enhances ShB resistance avoiding the phenotypic cost (Molla et al , ). Recently, Xu et al () devised another strategy to avert fitness costs due to AtNPR1 expression. The study demonstrated that the translational control of NPR1 gene by the uORFsTBF1 cassette, which comprises of an immune‐inducible promoter and two pathogen‐responsive upstream open reading frames, could engineer plant for disease resistance without compromising fitness penalty.…”
Section: Transgenic Approachmentioning
confidence: 99%
“…Agrochemical application is the most common method to mitigate biotic stresses in crop plants, but a more sustainable and environmentally friendly strategy is desirable (Xu et al, 2017). A promising approach to reduce such losses is to enhance the immune system of plants through genetic engineering, and this requires an improved understanding of the molecular mechanisms involved (Lacombe et al, 2010).…”
mentioning
confidence: 99%